Efficacy of imidacloprid, a new insecticide for controlling Myzus nicotianae on flue cured virginia tobacco (Nicotiana tabacum) - RAMAPRASAD, G; SRIDHEER, U; SITARAMAIAH, S; RAO, S NAGESWARA; SATYANARAYANA, V V (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-94 to evaluate the performance of a new insecticide imidaclopridand other insecticides for controlling tobacco aphid (Myzus nicotianae Blackman) on flue cured virginia tobacco (Nicotianatabacum L.). Both the formulations of imidacloprid (70 water soluble powder) and 200 soluble concentrates/litre at 50 gai or acephate 750 g ai/ha as 2 foliar sprays or combination of imidadoprid 70 water soluble powder at 100 g ai/ha asplant hole treatment + 1 foliar spray ofimidacloprid 200 soluble concentrates/litre at 50 g ai/ha effectively controlled theaphids throughout the season and recorded better yield of cured leaf, bright-leaf and grade index. Oxydemeton methyl0.05% foliar spray controlled the aphid effectively only up to 8 days after spray.